BILANGAN KROMATIK GRACEFUL PADA KELUARGA GRAF SENTRIPETAL - Lestari, Deninta Dwi Ayu; Kristiana, Arika Indah; Prihandini, Rafiantika Megahnia; Alfarisi, Ridho; Setiawan, Toto Bara; Adawiyah, Robiatul (Program Studi Matematika, Universitas Nusa Cendana, 2024)
One of the topics studied in graphs is graph coloring. The definition of a graceful coloring, namely k-elegant coloring of a graph G is the exact vertex coloring c:V(G)→ 1,2,...,k where k≥2 induces the exact vertex coloring c^': V(G)→ 1,2,...,k-1 which is defined by c(uv)=|c(u)-c(v)|. The exact vertex coloring c of a graph G is a graceful coloring if c is a k-elegant coloring for k∈N. The graceful chromatic number is the minimum k value where graph G has k-elegant coloring, the elegant chromatic number of graph G is denoted by X_g (G). This article will discuss graceful chromatic numbers in the centripetal graph family which includes octopus graph (O_n), sandat graph (St_n),dutch windmill graph (D_3^m) , and a volcano graph (V_n).